Consórcio de espécies nativas da floresta estacional semidecidual com mandioca (Manihot sculenta Crantz) para restauração de mata ciliar - Daronco, Camila [UNESP]; Galvao de Melo, Antonio Carlos; Rabelo Machado, Jose Arimateia (Univ Federal Vicosa, 2012)
Intercropping of trees and annual crops could be an important alternative for promoting forest restoration in small farms. The objective of this study was to evaluate the intercropping of cassava (Manihot sculenta Crantz) with native trees for restoration of natural forest in riparian areas in the western São Paulo State, Brazil. The experimental design was randomized blocks with six replications for comparing two restoration systems: pure afforestation and afforestation intercropped with cassava. It was evaluated the variables related to seedling development (height, crown diameter, crown cover, and height/crown diameter ratio), mortality and the economic impact were assessed for using cassava. No differences were found between treatments for any dendrometrical variable and mortality. Economic impact of the intercroppoing treatment was positive because costs for establishment of intercropped system were partially reduced by the income from the cassava crop, which covered 32% of total costs. Cassava income made final costs 19% lesser than restoration in the pure afforestation system.
Intercropping native tree species of seasonal semideciduous forest with cassava (Manihot sculenta Crantz) for restoriation of riparian forest
Keywords: Restoration ecology; Agroforestry and Taungya